MOLECULAR IDENTIFICATION OF PROTEOLITIC BACTERIA FROM MANGROVE SEDIMENT IN DUMAI MARINE STATION - Zebua, Abdi Hikmat Petra; Nursyirwani, Nursyirwani; Feliatra, Feliatra (Asian Journal of Aquatic Sciences, 2020)
Proteolytic bacteria have important role in the degradation of complex compounds to simple compound by the enzyme proteases. Sediment in mangrove ecosystem of Dumai Marine Station may contain the bacteria. This research aims to identify the proteolytic bacteria of mangrove sediments molecularly and to examine the antagonism of pathogenic bacteria. The method used in this research was survey. The results obtained 10 bacterial isolates (AZ1, AZ2, AZ3, AZ4, AZ6, AZ10, AZ11, AZ15, AZ18, and AZ20). Identification using 16S rRNA analysis revealed that 3 isolates showed different results, namely AZ2 had a similarity to Bacillus proteolyticus with strain MCCC 1A00365, AZ6 had a similarity to the bacteria B. monlinensis with strain BL4-6 and AZ20 had similarity to the bacterium B. toyonensis with strain MCCC 1A00365 BCT-7112. Three of the 10 isolates that had the highest inhibition against pathogens. Isolates AZ2 shovued inhibition zone against Pseudomonas aeruginosa with a diameter of 9.65 mm, AZ6 shovued inhibition zone against Escherichia coli bacteria with a diameter of 5.18 mm, and AZ20 shovued inhibition zone against Vibrio alginolyticus bacteria with a diameter of 4, 01 mm.